Optimizing Giri Cendana edutourism as support for the SDGs of Ngrancah Village - Anissa Hakim Purwantini; Farida Farida; Pranita Siska Utami (Community Empowerment, 2023)
Ngrancah Village has the potential for coffee education tourism, which is crucial for supporting the community's economic independence towards achieving the Village Sustainable Development Goals (SDGs). However, there are several challenges hindering business development, such as a lack of strong branding and insufficient knowledge among human resources regarding institutional and financial management. This results in the less organized running of edutourism. Additionally, partnerships and collaboration with village officials are not optimal, further hampering business development. This community service involves activities in the form of outreach, training, and mentoring based on Participatory Rural Appraisal (PRA). The outcomes of these community service activities are as follows: (1) Ngrancah Village's coffee edutourism now has strong branding, expanding its market share; (2) increased knowledge regarding institutional management, enabling members to fulfill their duties and collaborate with stakeholders for business development; and (3) enhanced knowledge and understanding of financial management, leading to the preparation of accountable and transparent financial reports.